High Variability of Molecular Isoforms of AMH in Follicular Fluid and Granulosa Cells From Human Small Antral Follicles - Mamsen, Linn Salto; Bøtkjær, Jane Alrø; Kristensen, Stine Gry; Pors, Susanne Elisabeth; Jeppesen, Janni Vikkelsø; Kumar, Ajay; Kalra, Bhanu; Ernst, Erik; Andersen, Claus Yding (Frontiers in Endocrinology, 2021)
Anti-Müllerian hormone (AMH) is a member of the TGF-β superfamily produced by follicular granulosa cells (GCs) in women from late gestation to the end of reproductive life. AMH is thought to inhibit aromatase (i.e., CYP19) expression and decrease the conversion of androgens to oestrogens, especially in small antral follicles before dominance is achieved. Thus, AMH acts as a gatekeeper of ovarian steroidogenesis. However, the exact function and processing of AMH has not been fully elucidated. The present study measured and determined AMH isoforms in human follicular fluid (FF) from small antral follicles and in human GCs using four ELISAs, western blot, and immunofluorescence analysis. We evaluated the presence of the following isoforms: full-length AMH precursor (proAMH), cleaved associated AMH (AMHN,C), N-terminal pro-region (AMHN), and active C-terminal (AMHC) AMH. A negative correlation between follicle diameter and the AMH forms was detected. Moreover, western blot analysis detected various AMH forms in both FFs and GCs, which did not match our consensus forms, suggesting an unknown proteolytic processing of AMH. The presence of these new molecular weight isoforms of AMH differs between individual follicles of identical size in the same woman. This study detected several AMH forms in FF and GCs obtained from human small antral follicles, which suggests that intrafollicular processing of AMH is complex and variable. Thus, it may be difficult to develop an antibody-based AMH assay that detects all AMH isoforms. Furthermore, the variability between follicles suggests that designing a recombinant AMH standard will be difficult.